Modifikasi Alat Ukur Addiction Smartphone (SAS) pada Subjek Emerging Adulthood - Saputra, Yoza Okta; Zulkarnain, Zulkarnain; Tarmidi, Tarmidi (Universitas Muhammadiyah Metro, 2025)
This study aims to modify the Smartphone Addiction Scale (SAS) measuring instrument compiled by Kwon et al (2013) which consists of 6 dimensions. The study used quantitative methods with a total of 258 respondents aged 17-26 years or are in emerging adulthood in Indonesia. Purposive sampling. Researchers modified the smart phone addiction measuring instrument (SAS) from 43 items to 49 items. Based on the results of the study, it was found that the content validity test showed 4 items were invalid, the item difference test resulted in 2 invalid items, and factor analysis of 5 invalid items. The final number of items is 38 items. The results of the multidimensional test show that the dimensions of interference in daily life have an r value of .857, positive anticipation has an r value of .810, withdrawal has an r value of .827, relationship orientation in cyberspace has an r value of .806, excessive use of smartphones has an r value of .848, and, tolerance has an r value of .765, whereas, the alpha reliability test results obtained a value of 0.937 and the modified smart phone addiction measuring instrument model is fit.